Research on Madrasas in International Publications: Bibliometric Analysis with Vosviewer - Zafrullah, Zafrullah; Zulfa Safina Ibrahim; Rezi Ariawan; Sa'adatul Ulwiyah; Rizki Tika Ayuni (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The large number of studies on madrasas on Scopus means that madrasas can be used as an option for researchers in conducting research. This research aims to look at the grouping and novelty of keywords using Vosviewer. This research used 323 documents that had been sorted according to keywords. From the results of the analysis, there are fourteen research groups based on keywords in madrasa research in the Scopus database, namely improving educational practices in madrasas, developing madrasa education in rural areas, preserving architectural heritage in madrasas, improving the Arabic language curriculum in Aliyah madrasas, Islamic pedagogy and practice. memorization, heritage preservation and restoration techniques, Islamic boarding school management, integration of character in online learning during the pandemic, madrasas and maktab religious education and national training, teacher performance and academic achievement, development of religious character, leadership in moral education, environmental learning in Muslim communities, as well as the study of Islamic history. Meanwhile, the novelty of keywords such as mausoleum, Islamic boarding schools, learners, character building, online learning, emotional intelligence, critical thinking skills, and learning outcomes indicates the novelty of the keywords so that these keywords can be used as research recommendations in research on madrasas in the Scopus database.